2024
DOI: 10.1007/s42844-024-00126-3
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Negotiation, Navigation Processes, and School Success in High School: A Two-Wave Latent Transition Approach

Wassilis Kassis,
Albert Dueggeli,
Christos Govaris
et al.

Abstract: By combining person-centered analysis with latent transition analysis (LTA) and adapting a navigation and negotiation perspective, we examined the effect of the COVID-19 pandemic on adolescents’ depression and anxiety levels as well as their adaptation and success in high school. Focusing on the navigation (individual adaptation) and negotiation (social adaptation) factors that contribute to school success, our data from a longitudinal study in Switzerland (wave 1 in autumn 2020, grade eight [n = 315]; wave 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Two interviewed participants moved up into a higher class (blooming and struggling, respectively), and one stayed in the struggling class. Yet, a low-support environment, as Theron [14] and Kassis et al [5] identified, consistently links to poor academic success, indicating that they may remain stable in their respective categories. These findings suggest that while high support might not invariably lead to high academic success, lower support systems correlate with diminished educational outcomes [5].…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Two interviewed participants moved up into a higher class (blooming and struggling, respectively), and one stayed in the struggling class. Yet, a low-support environment, as Theron [14] and Kassis et al [5] identified, consistently links to poor academic success, indicating that they may remain stable in their respective categories. These findings suggest that while high support might not invariably lead to high academic success, lower support systems correlate with diminished educational outcomes [5].…”
Section: Discussionmentioning
confidence: 95%
“…Yet, a low-support environment, as Theron [14] and Kassis et al [5] identified, consistently links to poor academic success, indicating that they may remain stable in their respective categories. These findings suggest that while high support might not invariably lead to high academic success, lower support systems correlate with diminished educational outcomes [5]. Moreover, there is neither a class low/high nor a student with low supportive indicators and high academic success.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations